2018
DOI: 10.1186/s12878-018-0127-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia and its associated factors in human immuno deficiency virus infected adult individuals in Ethiopia. A systematic review and meta-analysis

Abstract: BackgroundAnemia is a common hematologic disorder among human Immunodeficiency virus (HIV) infected adult Individuals. However, there is no concrete scientific evidence established at national level in Ethiopia. Hence, this review gave special emphasis on Ethiopian HIV infected adult individuals to estimate pooled prevalence of anemia and its associated factors at national level.MethodsStudies were retrieved through search engines in PUBMED/Medline, Cochrane Library, and the web of science, Google and Google s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 37 publications
(55 reference statements)
18
27
1
Order By: Relevance
“…Moreover, being female, having WHO clinical stage III or IV, having a BMI less than 18.5 kg/m 2 , having had an opportunistic infection, and taking AZT-containing ART drugs have significant associations with anemia. The magnitude of anemia found in this study is consistent with the findings of a systemic review of Ethiopia, which found the magnitude to be 31.0%; 27 a study conducted in Gondar, North West Ethiopia (22.4%); 28 and a study conducted in South Africa (25.8%). 5 This study's findings were lower than those of studies conducted in different health facilities in Ethiopia: Arba Minch (52.3%); 13 Dire Dawa (41.2%); 6 and Tikur Anbessa Specialized Hospital (34.6%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, being female, having WHO clinical stage III or IV, having a BMI less than 18.5 kg/m 2 , having had an opportunistic infection, and taking AZT-containing ART drugs have significant associations with anemia. The magnitude of anemia found in this study is consistent with the findings of a systemic review of Ethiopia, which found the magnitude to be 31.0%; 27 a study conducted in Gondar, North West Ethiopia (22.4%); 28 and a study conducted in South Africa (25.8%). 5 This study's findings were lower than those of studies conducted in different health facilities in Ethiopia: Arba Minch (52.3%); 13 Dire Dawa (41.2%); 6 and Tikur Anbessa Specialized Hospital (34.6%).…”
Section: Discussionsupporting
confidence: 89%
“…This finding is in line with study reports from Malawi, 35 South Africa, 5 and Ethiopia. 6,27 Lower BMI reflect undernutrition as a result of low calorie intake, poor absorption, or poor utilization of nutrients, which leads to insufficient levels of iron, folate, and vitamin B-12 for erythrocyte production. In addition, having a lower BMI increases the risk of infections, which can contribute to the occurrence of anemia.…”
Section: Discussionmentioning
confidence: 99%
“…These search terms were pre-defined to allow a comprehensive search strategy that included all fields within records and Medical Subject Headings (MeSH terms), in order to expand the search in an advanced PubMed search (Appendix). Following the search protocol described by Negesse et al [22], we also used Boolean operator in our search as they outline in their paper: “within each axis we combined keywords with the ‘OR’ operator and we then linked the search strategies for the two axes with the ‘AND’ operator to search studies conducted specifically for each region in the country”. Electronic database searches were conducted from September 1, 2018 to November 10, 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Studies suggest that cytopenias especially anemia1, 8 , 11 , 14 25 (prevalence ranging from 1.3% to 95% globally, 21 and 23.9% to 38.0% (31.0% pooled) in Ethiopia 19 before or at the start of highly active antiretroviral therapy (HAART)) would frequently occur in HIV-1 infected patients, mainly during advanced stages of the disease. The occurrence and magnitude of these hematologic abnormalities are likely dependent on the level of viral replication, associated with worsening of the clinical conditions in late-stage AIDS patients with high-level viremia.…”
Section: Introductionmentioning
confidence: 99%